Diagnostic value of early postoperative color doppler ultrasonography to predict vascular complications following liver transplantation - Nejatollahi , Seyed Mohammad Reza; Khoshkholgh Sima , Maryam; Peirovi, Habibollah; Niaghi , Farhad (Researcher Bulletin of Medical Sciences, 2020)
Introduction: Blood flow and hemodynamic of the transplanted liver has an important predictive role in the survival of the patients. We aimed to determine the diagnostic value of early post-operative color doppler ultrasonography (CDU) for detecting vascular complications following liver transplantation at our center. Materials and Methods: In this prospective study, consecutive patients who underwent deceased donor liver transplantation between March 2016 and March 2017 were enrolled. Color Doppler ultrasonography was performed within the first week following surgery. The follow-up CDU was performed after 1 year from the liver transplantation. Using the ﬁndings of follow up CDU as the reference standard, we calculated values of the capability of the initial CDU in the diagnosis of the hepatic artery, portal vein and intrahepatic veins’ stenosis, including the level of agreement, sensitivity, speciﬁcity, positive predictive value, negative predictive value, and diagnostic accuracy. Results: The data of 50 patients were analyzed in this study (mean age=38.9±13.2 years, 26 [52%] men). In the initial ultrasonography, 16 cases had hepatic artery stenosis, 4 cases had portal vein stenosis and 4 patients had IVC stenosis. The diagnostic value of the early postoperative CDU for hepatic artery stenosis, portal vein stenosis, and other vascular stenosis were 71.9, 96.0, and 62.0, respectively. Conclusion: Early post-operative CDU is a safe and feasible method that can detect the development of hepatic artery or portal vein stenosis in liver transplant recipients with a low to moderate positive predictive value and a high negative predictive value.